İşletmelerde Muhasebe Bilgi Sistemine Yaklaşım - (:unkn) unknown (My University, 2005)
Yapılan bu çalışmanın amacı işletmelerde muhasebe uygulamalarında yeni bir alan olan Muhasebe Bilgi Sistemlerine Yaklaşımı irdelemektir. Muhasebe Bilgi Sistemleri işletme organizasyonlarının bir alt sistemi olan Yönetim Bilgi Sistemlerinin, bir çeşit alt sistemidir.işletmelerin varlıkları arasında önemli olan veri ve bilginin, veri güvenirliği ve emniyetiyle ilgili olması sadece muhasebecilerin değil aynı zamanda tüm mesleki bilgi sistemleriyle de ilgilidir.

The aim of this study is to present the Accounting Information Systems(AIS) and approach in companies which is the new area in the accountancy practices. The Accounting Information Systems is a kind of subsystem within the organization's Management Information Systems (MIS) which in itself is a subsystem of the organization. Data-base and information are among a company's most important assets that concern about data reliability and security are relevant not only to accountants, but also to all information systems professionals. On the other hand accountant are auditors.
An Approach to Accounting Information Systems in Business
Keywords: Bilgisayar Bilimleri, Bilgi Sistemleri; İş; İşletme Finans; İktisat; Bilgi, Belge Yönetimi